Respuesta :
You are looking for
x × ? = 3x^2
and
-4 × ? = 8
The first one is x × 3x = 3x^2
second one is -4 × -2 = 8
So your factored expression is
(x - 2)(3x - 4)
x × ? = 3x^2
and
-4 × ? = 8
The first one is x × 3x = 3x^2
second one is -4 × -2 = 8
So your factored expression is
(x - 2)(3x - 4)
Answer: The complete factorization of the given expression is [tex](x-2)(3x-4).[/tex]
Step-by-step explanation: We are given to complete the factorization of the following quadratic expression :
[tex]E=3x^2-10x+8~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
To factorize the given expression, we need two integers with sum -10 and product 34. Those two integers are -6 and -4.
The factorization of expression (i) is as follows :
[tex]E\\\\=3x^2-10x+8\\\\=3x^2-6x-4x+8\\\\=3x(x-2)-4(x-2)\\\\=(x-2)(3x-4).[/tex]
Thus, the complete factorization of the given expression is [tex](x-2)(3x-4).[/tex]